Pengaruh Brand Image Dan Brand Ambassador Terhadap Keputusan Pembelian Kosmetik Wardah Pada Sashop Gorontalo - Safitri Afifa Putri Satriyo; Hasanuddin Hasanuddin; Elfis Mus Abdul (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research seeks to examine the impact of brand image and brand ambassadors on the purchasing decisions of Wardah cosmetics consumers at Sashop Gorontalo. Data were gathered using questionnaires distributed to Wardah customers at Sashop Gorontalo. The independent variables in this study are brand image and brand ambassador, while the dependent variable is purchasing decision. The research population consists of 97 respondents selected through a purposive sampling method. Instrument testing involved assessments of validity and reliability. The data were analyzed using multiple linear regression with the assistance of SPSS 25 software. The results of the t-test reveal that brand image and brand ambassador each have a significant individual effect on purchasing decisions. Additionally, the F-test results demonstrate that both variables together significantly influence purchasing decisions